Carbonate and terrigenous sediment budgets for inshore turbid reefs on the central Great Barrier Reef - Browne, Nicola; Smithers, S; Perry, C (Elsevier Science BV, 2013)
Inshore turbid zone reefs on the Great Barrier Reef (GBR) occur within 20 km of the mainland coast under marine environmental conditions (with respect to sedimentation rates, turbidity and water quality) that are generally considered marginal for reef growth. Despite this, data from various benthic habitat assessments report high (N30%) coral cover in these environments and reef core records show them to be characterised by relatively rapid rates of vertical accretion (2–8 mm/year), a long-term trend indicative of high net carbonate productivity and in-situ carbonate framework accumulation. However, the lack of quantitative data on terrigenous sediment input and flux rates, and on carbonate production rates has inhibited understanding of both ecological timescale rates of carbonate production and the aggregated long-term net impacts of sediments on reef growth. To address this knowledge gap a modern carbonate budget and terrigenous sediment model, that quantified allochthonous sediment inputs onto, within and off reef, was developed at two inshore reefs: Middle Reef and Paluma Shoals. Both are located within the central region of the GBR and are subjected to high terrigenous sediment load (N11,000 tonnes/year) and fluctuating turbidity (5 to N100 mg/L) regimes.Based on sediment dynamic modelling, over 81% of sediments delivered were transported off reef, with net sediment accumulation limited to sheltered reef habitats. Net carbonate production was high (N6.9 kg/m2/year) due to high coral cover (N30%), high coral calcification rates (Acropora average 6.3 g/cm2/year), and low bioerosion rates (0.3 to 5 kg/m2/year), but varied spatially with highest net carbonate production (N10 kg/m2/year) within deep (N-2 m at LAT) windward reef zones. High carbonate framework production has enabled Middle Reef and Paluma Shoals to vertically accrete rapidly: Middle Reef establishing at depths of ~4 m, Paluma Shoals at ~3 m depth and both reaching sea level in b1200 years. Carbonate and terrigenous sediment inputs were used to develop a reef growth model with time and depth that illustrates how rates and modes of reef growth varied temporally as the reefs approached sea level. Both Middle Reef and Paluma Shoals are still actively accreting, although vertical reef growth potential is increasingly constrained as the reef flats infill at present sea level.